THE EFFECT OF CORPORATE GOVERNANCE, FINANCIAL RATIO, FIRM SIZE AND AUDIT QUALITY ON BOND RATING - MUNGNIYATI MUNGNIYATI; ARYA PRADIPTA (Media Bisnis, 2013)
This purpose of this research is to examine the effects of corporate governance, financial condition, firm size and audit quality on corporate bond ratings in Indonesia. Corporate governance is explored in term of institutional ownership, managerial ownership, independent commissioner, and audit committee. Moreover, several accounting ratios including current asset, return on asset, debt to equity, and interest coverage are used to reflect corporate financial condition. Data are collected from PT Pefindo and Indonesia Stock Exchange during 2005 until 2009. The result shows that institutional ownership, managerial ownership, audit committee, return on asset, debt to equity ratio, firm size and audit quality have a significant influence on bond ratings. This finding suggests that the implementation of good corporate governance, maintaining a sound financial condition, firm size and audit quality are very important for getting better corporate bond ratings in Indonesia.